Characteristics of Phytoplankton Community Structure and Indication to Water Quality in the Lake in Agricultural Areas - Huang, Yiqiang; Shen, Yucheng; Zhang, Shouzhi; Li, Yang; Sun, Zeyu; Feng, Mingming; Li, Rui; Zhang, Jin; Tian, Xue; Zhang, Wenguang (Frontiers in Environmental Science, 2022)
In recent years, lakes' water quality and quantity have been affected and damaged by agricultural activities. The sensitivity of phytoplankton to the hydrological environment can effectively indicate the health of the aquatic ecosystem and the change in water quality. To clarify the correlation between phytoplankton and environmental factors in the lake adjacent to agriculture area and confirm the indicative function of the phytoplankton community on water quality, in this research, redundancy analysis (RDA), functional groups, and biodiversity index was used to analyze the characteristics of phytoplankton community in Xinmiao Lake. It is found that there are 146 species, 63 genera, and 8 phyla of phytoplankton, including 57 species of Bacillariophyta, 46 species of Chlorophyta, 17 species of Cyanophyta and Euglenophyta. The total abundance was changed successively with Bacillariophyta (75% in Jun.), Cyanophyta (50% in Jul.–Aug.), and Chlorophyta (75% in Sep.–Oct.). The total biomass decreased continuously over time. The biomass of green algae is highest in October(67.4%), and diatoms contribute the most biomass in other months (76.5%). The Redundancy analysis indicated that the main environmental factors affecting phytoplankton's dynamic change are salt content, water temperature, total phosphorus, and five-day biochemical oxygen demand. The phytoplankton can be divided into 21 functional groups. The MP group has the highest frequency, mainly distributed in the frequently stirred and turbid shallow water. Representative functional groups indicate the high degree of eutrophication and nutrient content and the good associated environment of hydrophyte and slow water flow rate. With the seasonal change of agricultural irrigation and drainage, the water quality of Xinmiao Lake began to deteriorate from medium pollution in July and reached serious pollution in October finally. Furthermore, this research discovered that the risk of cyanobacteria bloom is high in summer, primarily when thermal stratification occurs. This study provides necessary information for understanding and predicting the changes of the phytoplankton community caused by the increase of nutrients, human disturbance, and temperature conditions in eutrophic lakes in agricultural areas.